PREDICAMENT OF DOCTORS; DISCERNING BURNOUT LEVEL AMONGST SURGICAL RESIDENTS OF KARACHI, PAKISTAN - Zaheer, Farhan; Aziz, Imrana; Arif, Sarah; Khan, Mohammad Omer; Khan, Anosh Aslam; Osama, Muhammad; Naseer, Shafaq; Sheikh, Mahnoor Yousif (Journal of Ayub Medical College Abbottabad, 2020)
Background: Stress and burnout have been soaring among doctors. It does not only have deleterious effects during working hours but also impact personal lives of the doctors. The primary focus of this study is to gauge level of burnout among surgical residents working in two major tertiary care hospital of Karachi, Pakistan. Methods: This was a cross sectional study comprising of 118 candidates who completed the questionnaire based on demographics variables, professional details and Maslach Burnout Inventory (MBI), which scores the burnout level on the basis of three components namely emotional exhaustion, depersonalization and personal accomplishment. The duration of study was one month starting from 1st January to 31st January 2019. Residents working in Department of General Surgery were part of inclusion criteria. Consultants and medical students met the exclusion criteria. Data was analysed by SPSS-23. Results: Mean MBI score was 57.15 with mean scores of Emotional Fatigue, Personal Fulfilment and Depersonalization were 22.42, 19.89 and 14.81 respectively. In terms of emotional fatigue, female residents (49.2%) were more likely to suffer than their male counterpart (50.8%) (p=0.018). Married residents (37.3%) tend to have higher mean personal fulfilment scores (p=0.02). Residents who were living alone (31%) have higher mean depersonalization score (p=0.02). With respect to personal factors, higher MBI scores were observed among doctors who were married, worked about 75-90 hours and remain sleep-deprived and those who were not able to sustain their families financially. Conclusion: On the basis of higher MBI scores in married, sleep deprived residents who were working for extensive hours and felt financial constraints, there is an extensive need of comprehensive support groups, humane number of working hours, improved salary packages, de-stressing activities like sports etc. to ameliorate the mental health of resident physicians and enhance their productivity. Keywords: Burnout; Residents; Surgery; Karachi